2020
DOI: 10.1088/1361-6463/ab71a8
|View full text |Cite
|
Sign up to set email alerts
|

Eco-efficiency analysis of plasma-assisted nitrogen fixation

Abstract: An eco-efficiency analysis has been conducted, as a sustainability performance indicator, by combining the life cycle costs (LCC) and the environmental impacts of diverse plasma-assisted ammonia and nitric acid synthesis routes, for which a detailed process design for small-scale production has been previously reported. The proposed design of the specific plasma processes involves new upstream and downstream activities, which are independent of conventional natural resources and comprise less equipment. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…On the other end of the commercial food chain, low-temperature plasma processes have shown promise for the nitrogen fixation to fertilizers. [24,[37][38][39][40] While they seem to be on the way to give an economic pathway to nitric acid as platform material for fertilizers recent plasma technologies did not manage to produce truly green and affordable ammonia. [41][42][43] Having both ammonia and nitric acid would open the full N-based fertilizer plethora from urea, ammonium nitrate, potassium nitrate, and so on.…”
Section: National Drivers Of Local Fertilizer Economy: the Australian Situationmentioning
confidence: 99%
“…On the other end of the commercial food chain, low-temperature plasma processes have shown promise for the nitrogen fixation to fertilizers. [24,[37][38][39][40] While they seem to be on the way to give an economic pathway to nitric acid as platform material for fertilizers recent plasma technologies did not manage to produce truly green and affordable ammonia. [41][42][43] Having both ammonia and nitric acid would open the full N-based fertilizer plethora from urea, ammonium nitrate, potassium nitrate, and so on.…”
Section: National Drivers Of Local Fertilizer Economy: the Australian Situationmentioning
confidence: 99%
“…Smaller, decentralized plants could be co-located with fertigation systems to produce and distribute fertilizer only when necessary and could also be adapted for localized climates and conditions. 20 The use of plasma-xated nitrogen systems will allow for the development of sustainable decentralized production on site. These decentralized plants would be able to be integrated into fertigation systems and produce and distribute fertilizer only when necessary.…”
Section: Field Integrationmentioning
confidence: 99%
“…Economic analysis of the energy costs and efficiencies have been extensively studied for a variety of plasma xation technologies. 18,20 These past studies have shown potential in realizability of scalable production based on estimated capital expenses and operating costs. The current Haber-Bosch process has been fully optimized over the past century of its use, with an energy consumption of about 0.48 MJ mol À1 ammonia produced.…”
Section: Field Integrationmentioning
confidence: 99%
“…[20] Adding the energy consumption of reactants production (0.51 MJ mol À1 NH 3 ) and product separation (0.54 MJ mol À1 NH 3 )results in atotal energy consumption of 19.65 MJ mol À1 NH 3 as shown in Figure 2. [21] Theenergy consumption of PNOCRA is an over 4-fold reduction, compared to the current BATf or plasmabased NH 3 synthesis.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[19] Ther ecovery of NH 3 from such ad iluted product mixture would be very challenging and highly energy intensive.The lowest reported energy cost with areasonable yield (1.4 %) is 18.6 MJ mol À1 NH 3 . [20] Al ow ammonia concentration in the reactor outlet can increase dramatically the overall energy consumption of the ammonia synthesis process.A nastasopoulou et al [21] quantified this energy penalty.F or amixture with 1vol %NH 3 ,the energy needed for NH 3 separation from such ad iluted gas mixture is in the range of the energy consumption of the Haber-Bosch process (0.54 MJ mol À1 NH 3 ). [21] Thehigh energy demand of plasma-driven NH 3 synthesis in its current state calls for an alternative approach.…”
Section: Introductionmentioning
confidence: 99%